Hala tuju seni seramik di Malaysia dalam era kontemporari - Afandy, Bin Che Manah. (Universiti Malaysia Sarawak (UNIMAS), 2007)
This research is an artwork which is about a huge cooking lltensillisedfor cooking plllposes in a Malay village feast. The artwork entitle Kawah is produced to signifY the great unity sense happened during the communal activity.